Role of Folklore in Teaching English for Pre-School Children (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
The article describes the role of folklore in teaching English for pre-school children. English folklore for children has some distinguishing features, which differ it from the folklore of other people. If the distinguishing feature of the German, Russian, Scandinavian folklore is fairy tales.